Using Critical Discourse Analysis (CDA) in Media Discourse Studies: Unmask the Mass Media - Emi Sahmeni; Nur Afifah (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2019)
The purpose of this paper is to know how CDA unraveling the covert ideologies while researching the existence of power in media discourse studies. This study reviewed sixteen journal articles to examine the ways and methods to discover the social phenomenon while revealing the authentic identity of the social actors. It was found that CDA has been used extensively to unmask the ideologies which classify the oppressed group while presenting a positive image for the group with the highest authority. The theory proposed by Teun Van Dijk seems the most used theories used when it related to unmask the media profiling. There are three elements in the theory of CDA Van Djik that plays an important role in the research is Macrostructure, superstructure and microstructure. This study manage to reveals that mass media play an important role in the production of trust, prejudice and dominance over social contexts.